Embracing the Wisdom of Ancient Greece in the Era of Personalized Medicine—Uncertainty, Probabilistic Reasoning, and Democratic Consensus - Maarten Naesens (Transplant International, 2023)
Further improvements of outcome after solid organ transplantation will depend on our ability to integrate personalized medicine in clinical routine. Not only better risk stratification or improved diagnostics, also targeted therapies and predictive markers of treatment success are needed, as there is a virtual standstill in the development and implementation of novel therapies for prevention and treatment of allograft rejection. The integration of clinical decision support algorithms and novel biomarkers in clinical practice will require a different reasoning, embracing concepts of uncertainty and probabilistic thinking as the ground truth is often unknown and the tools imperfect. This is important for communication between healthcare professionals, but patients and their caregivers also need to be informed and educated about the levels of uncertainty inherent to personalized medicine. In the translation of research findings and personalized medicine to routine clinical care, it remains crucial to maintain global consensus on major aspects of clinical routine, to avoid further divergence between centres and countries in the standard of care. Such consensus can only be reached when experts with divergent opinions are willing to transcend their own convictions, understand that there is not one single truth, and thus are able to embrace a level of uncertainty.